\[\boxed{\mathbf{727\ (727).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a_{1} = - 6;\ \ a_{3} = 12\]
\[a_{n} = \frac{a_{n - 1} + a_{n + 1}}{2}\ \]
\[a_{2} = \frac{a_{1} + a_{3}}{2} =\]
\[= \frac{- 6 + 12}{2} = \frac{6}{2} = 3.\]
\[Ответ:a_{2} = 3.\]
\[\boxed{\mathbf{727.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ \sqrt{(a - b)^{2}} + \sqrt{16a^{2}};\ \ a < 0;\ \]
\[\ b > 0\]
\[\sqrt{(a - b)^{2}} + \sqrt{16a^{2}} = |a - b| +\]
\[+ 4|a| = b - a - 4a = b - 5a.\]
\[2)\ \sqrt{(x - y)^{2}} - \sqrt{9y^{2}};\ \ x > 0;\ \ \]
\[y < 0\]
\[\sqrt{(x - y)^{2}} - \sqrt{9y^{2}} = |x - y| -\]
\[- 3|y| = x - y + 3y = 2y + x.\]